Spanish mental health nurses' experiences of mechanical restraint: A qualitative descriptive study. Issue 5 (28th July 2022) - Pérez‐Toribio, Alonso; Moreno‐Poyato, Antonio R.; Roldán‐Merino, Juan F.; Nash, Michael
Accessible Summary: What is known on the subject?: Mechanical restraint is a common practice in mental healthcare settings in Spain, despite controversy. Mechanical restraint is perceived as a negative experience for nurses and service users. Mechanical restraint damages the nurse–patient therapeutic relationship, which is essential in providing quality care and promoting recovery. What the paper adds to existing knowledge?: The negative experiences of service users and mental health nurses arising from use of mechanical restraint affects both parties involved and results in trauma. Using mechanical restraint can provoke a moral injury in mental health nurses which can negatively impact on the establishment of trust within the therapeutic nurse–patient relationship. What are the implications for practice?: Nurses must be aware of the negative effects that mechanical restraint use has on both their practice and their day‐to‐day lives. Post‐mechanical restraint debriefing is required to repair the damage to the trust aspect of the nurse–patient relationship. Involving service users in co‐producing a debriefing framework may be a way to rebuild trust through constructive dialogue. Abstract: Introduction: Mechanical restraint is an intervention that causes harm to service users and nurses, yet continues to be used in many countries, including Spain. However, there is a lack of research exploring Spanish mental health nurses' experiences of using mechanical restraint. Aim: To describe the experiences of mental health nurses who have used mechanical restraint in practice. Methods: A qualitative descriptive methodology was used and a purposive sample of 10 Spanish mental health nurses were interviewed about their experiences of using mechanical restraint. Thematic analysis was then employed to analyse interview data. Results: Participants' experiences of using mechanical restraint were mostly negative. Three main themes arose from the analysis of interview transcripts, (i) symmetrical trauma, (ii) moral injury and (iii) broken trust. Discussion: The use of restrictive practices, which can be perceived as counter‐therapeutic, exposes nurses to risks such as moral injury and service users to broken trust in the therapeutic nurse patient relationship. Avoiding empathy in order to use mechanical restraint is counterproductive, in the understanding that empathy is key to reducing this intervention. Implications for practice: Reducing or eliminating use of mechanical restraints should be a policy and practice priority due to the symmetrical harms it causes both nurses and service users. The trust aspect of the therapeutic nurse–patient relationship is a significant casualty when mechanical restraint is used, therefore involving service users in co‐production of post‐mechanical restraint debriefing can be an avenue for restoring this trust through dialogue.